2017
DOI: 10.1097/mat.0000000000000443
|View full text |Cite
|
Sign up to set email alerts
|

LVAD Outflow Graft Angle and Thrombosis Risk

Abstract: This study quantifies thrombogenic potential of a wide range of LVAD outflow graft anastomosis angles through. This study aims at clarifying the influence of a single parameter (outflow graft angle) on the thrombogenesis associated with flow patterns in the aortic root after LVAD implantation. This is an important and poorly-understood aspect of LVAD therapy, because several studies have shown strong inter-and intra-patient thrombogenic variability and current LVAD implantation strategies do not incorporate ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 76 publications
(81 citation statements)
references
References 55 publications
2
78
0
Order By: Relevance
“…While the results highlighted here are for the subset of particles traveling towards the cerebral circulation, the trends are fully consistent with statistics for all platelets, and irrespective of outflow graft angle 14 : intermittent AV opening has a globally beneficial effect on both RT and SH for all injected particles.…”
Section: Resultssupporting
confidence: 78%
See 3 more Smart Citations
“…While the results highlighted here are for the subset of particles traveling towards the cerebral circulation, the trends are fully consistent with statistics for all platelets, and irrespective of outflow graft angle 14 : intermittent AV opening has a globally beneficial effect on both RT and SH for all injected particles.…”
Section: Resultssupporting
confidence: 78%
“…CFD simulations of blood flow, including platelet-surrogate dynamics, are performed for the different conditions 14 . Briefly, image segmentation was performed on Gadolinium-enhanced magnetic resonance angiography (MRA) images of patient vasculature of the ascending aorta and great vessels.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies conducted where the AV remained closed found that stagnation typically occurs immediately distal to the AV [11, 14, 34]. A previous study by our group followed up on these results demonstrating that including residual cardiac function in the simulation eliminated stagnation [35]. This finding demonstrates the importance of optimizing VAD speed to allow for intermittent AV opening.…”
Section: Discussionmentioning
confidence: 74%